2008
DOI: 10.1007/s12272-001-1283-5
|View full text |Cite
|
Sign up to set email alerts
|

Morin protects acute liver damage by carbon tetrachloride (CCl4) in rat

Abstract: The purpose of this study was to investigate possible beneficial effects of morin on CCl(4)-induced acute hepatotoxicity in rats. Rats received a single dose of CCl(4) (150 microL/100 g 1:1 in corn oil). Morin treatment (20 mg/kg) was given at 48, 24, and 2 h before CCl(4) administration. CCl(4) challenge elevated serum alanine transaminase (ALT), aspartate transaminase (AST), and alkaline phosphatase (ALP) levels, but these effects were prevented by the pretreatment of rats with morin. To identify the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 27 publications
3
20
0
1
Order By: Relevance
“…Their data were supported by Harasstani et al, who found the inhibition of NO production by morin in LPSinduced RAW 264.7 cells [20]. Similar results were also demonstrated by Lee and Aliev et al [30,31]. PGE 2 is also an inflammatory factor which is elevated by COX-2.…”
Section: Discussionsupporting
confidence: 66%
“…Their data were supported by Harasstani et al, who found the inhibition of NO production by morin in LPSinduced RAW 264.7 cells [20]. Similar results were also demonstrated by Lee and Aliev et al [30,31]. PGE 2 is also an inflammatory factor which is elevated by COX-2.…”
Section: Discussionsupporting
confidence: 66%
“…[14] Since the changes associated with CCl 4 -induced liver damage are similar to that of acute viral hepatitis,[15] CCl 4 -mediated hepatotoxicity was chosen as the experimental model. [1617] It has been established that CCl 4 is accumulated in hepatic parenchyma cells and metabolically activated by cytochrome P450-dependent monooxygenases to form a trichloromethyl radical (CCl 3 ). The CCl 3 radical alkylates cellular proteins and other macromolecules with simultaneous attack on polyunsaturated fatty acids, in the presence of oxygen, to produce lipid peroxides, leading to liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…The largest lobe of the livers was sliced, and tissue slices were fixed in 10% neutral buffered formalin, then embedded in paraffin, sectioned 3-4 μm and stained with hematoxylin and eosin (HE) and Sirius red (SR) for general histopathology or with masson's trichrome (MT) for collagen fiber. (11,12) The histopathological profiles of each sample were observed under light microscope (Nikon, Japan).…”
Section: Histopathologymentioning
confidence: 99%